Z‐scheme CuSbS2/ZnO Heterojunction for Enhanced Photocatalytic Degradation of RhB. Issue 29 (2nd August 2022) - Zhi, Guowei; Hao, Lingyun; Chen, Wenjing; Sheng, Qinyang; Liu, Liu; Wang, Wei; Yao, Hanyu
Abstract: The heterojunction structure photocatalysts are very promising for photocatalytic degradation dyes to resolve the organic industrial wastewater. In this work, an effective and solar light‐driven Z‐scheme heterojunction photocatalyst CAS/ZnO was prepared by two steps microwave irradiation method. The ZnO nanosheets were successfully compounded with CAS tetragonal particles aggregate. As the ZnO concentration increased, the absorbance decreased but the specific surface area increased. Rhodamine B (RhB) was tested for photodegradation by photocatalysts under a solar simulation in 120 min, and 3 M displayed the highest degradation rate (100 %), highest rate constant (0.021 min −1 ) and optimum stability. Furthermore, the main reactive species were superoxide radicals (O2 −. ) and hydroxyl radicals (HO⋅). Also, mechanism of the Z‐scheme migration of photon‐generated carrier and photocatalytic degradation was proposed. This paper provides a new Z‐scheme heterojunction CAS/ZnO photocatalyst for the treatment of organic pollutants. Abstract : In this work, an effective and solar light‐driven Z‐scheme heterojunction photocatalyst CAS/ZnO was prepared by two steps microwave irradiation method. As the ZnO concentration increased, the absorbance decreased but the specific surface area increased. 3 M displayed the highest degradation rate (100 %), highest rate constant (0.021 min −1 ) and optimum stability. Also, mechanism of the Z‐scheme migration of photon‐generated carrier and photocatalytic degradation was proposed. This paper provides a new Z‐scheme heterojunction CAS/ZnO photocatalyst for the treatment of organic pollutants